2011
DOI: 10.2344/0003-3006-58.2.73
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind Placebo-Controlled Comparison of a Novel Formulation of Intravenous Diclofenac and Ketorolac for Postoperative Third Molar Extraction Pain

Abstract: Dyloject is a novel formulation of diclofenac intended for intravenous ( IV) administration. This formulation employs the solubilizing agent hydroxypropyl-b-cyclodextrin to permit bolus IV administration. The efficacy and safety of 5 dose levels of IV diclofenac were compared with IV ketorolac and placebo following third molar extraction. This was a single-dose, randomized, double-blind, placeboand comparator-controlled, parallel-group study. A total of 353 subjects with moderate to severe pain received placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…Diclofenac is used in moderate to severe pain following third molar extraction and it could be used in an intravenous form in risk population groups such as the elderly and renal insufficiency, postoperative anticoagulation which uses ketorolac as the only choice for the moderate to severe acute pain. Very similar effects were shown when transdermal diclofenac patches were used compared to oral administration [99,100].…”
Section: Analgesic Monotherapy Versus Combined Therapy In Dental Pracsupporting
confidence: 50%
“…Diclofenac is used in moderate to severe pain following third molar extraction and it could be used in an intravenous form in risk population groups such as the elderly and renal insufficiency, postoperative anticoagulation which uses ketorolac as the only choice for the moderate to severe acute pain. Very similar effects were shown when transdermal diclofenac patches were used compared to oral administration [99,100].…”
Section: Analgesic Monotherapy Versus Combined Therapy In Dental Pracsupporting
confidence: 50%
“…In two separate double-blind placebo-controlled trials in patients undergoing third-molar extraction, HPbCD-diclofenac had a faster onset of pain relief than either Voltarol 21 or ketorolac. 24 More recently, HPbCDdiclofenac showed a faster onset of action than IV ketorolac in a population of patients having undergone orthopedic surgery. 25 The lower incidence of thrombophlebitis with HPbCD-diclofenac compared with Voltarol and subsequent reduced need for treatment of adverse events, as well as HPbCD-diclofenac's lack of need for reconstitution, dilution, and buffering prior to each dose compared with Voltarol provide support for potential cost savings with HPbCD-diclofenac compared with Voltarol.…”
Section: Discussionmentioning
confidence: 99%
“…14 In the development program for HPbCD diclofenac, a single 37.5 mg dose was significantly more efficacious than placebo in a molar-extraction pain model. 15 Subsequently, a randomized, multiple-dose trial demonstrated the safety and superior efficacy, relative to placebo, of HPbCD diclofenac 18.75 and 37.5 mg when used for acute moderate and severe pain after major abdominal or pelvic surgery. 16 The objective of the current trial was to investigate HPbCD diclofenac for treatment of moderate and severe pain after elective orthopedic surgery.…”
mentioning
confidence: 99%